Effects of Anxiety and Learning Styles on Foreign Language Testing: Case of Work-Study Contract Students - karine LONGIS MCMILLAN (Journal of Educational, Health and Community Psychology, 2021)
Studies have proved multiple times that anxiety and different learning styles within the FL classroom affect students when they are doing a test. These studies however have not yet observed every different kind of students. With this context, data were collected from 71 work-study contract vocational higher diploma students from EFIATP Correze, France during the 2020-2021 academic years. As a conclusion of this study, it is determined that there are no significant relationships between the FL student anxiety in the classroom, their learning styles and their test Level.Keywords: FL , foreign language , anxiety, learning styles, test level, work-study contract students